Exosome-Guided Phenotypic Switch of M1 to M2 Macrophages for Cutaneous Wound Healing - Kim, Hyosuk; Wang, Sun Young; Kwak, Gijung; Yang, Yoosoo; Kwon, Ick Chan; Kim, Sun Hwa (WILEY, 2019)
Macrophages (M phi s) critically contribute to wound healing by coordinating inflammatory, proliferative, and angiogenic processes. A proper switch from proinflammatory M1 to anti-inflammatory M2 dominant M phi s accelerates the wound healing processes leading to favorable wound-care outcomes. Herein, an exosome-guided cell reprogramming technique is proposed to directly convert M1 to M2 M phi s for effective wound management. The M2 M phi-derived exosomes (M2-Exo) induce a complete conversion of M1 to M2 M phi s in vitro. The reprogrammed M2 M phi s turn Arginase (M2-marker) and iNOS (M1-marker) on and off, respectively, and exhibit distinct phenotypic and functional features of M2 M phi s. M2-Exo has not only M phi reprogramming factors but also various cytokines and growth factors promoting wound repair. After subcutaneous administration of M2-Exo into the wound edge, the local populations of M1 and M2 M phi s are markedly decreased and increased, respectively, showing a successful exosome-guided switch to M2 M phi polarization. The direct conversion of M1 to M2 M phi s at the wound site accelerates wound healing by enhancing angiogenesis, re-epithelialization, and collagen deposition. The M phi phenotype switching induced by exosomes possessing the excellent cell reprogramming capability and innate biocompatibility can be a promising therapeutic approach for various inflammation-associated disorders by regulating the balance between pro-versus anti-inflammatory M phi s.
Keywords: EXTRACELLULAR VESICLES; DENDRITIC CELLS; GROWTH-FACTOR; POLARIZATION; ACTIVATION; EXPRESSION; MONOCYTE; CCL11